in Impaired Pulmonary Oxygenizing Function in Cardiosurgical Patients - I. A. Kozlov; A. A. Romanov; O. A. Rozenberg (Общая реаниматология)
Objective: to study the impact of administration of surfactant-BL, followed by alveolar mobilization on the parameters of pulmonary oxygenizing function and biomechanics in patients with impaired lung oxygenizing function (ILOF) in the early postoperative period. Subjects and methods. Eight patients aged 48—73 years (mean 59.1±3.0 years) were examined. The indication for alveolar mobilization was an oxygenation index (PaO2/FiO2) of less than 300 mm Hg during artificial ventilation (AV). Alveolar mobilization was carried out under AV, by regulating from the pressure to achieve its airways maximum of 31.6± 1.2 cm H2O and a PEEP of 16.4±0.4 cm H2O. The indication for the use of surfactant-BL (Biosurf, Saint Petersburg) was a reduction of PaO2/FiO2 below 300 mm Hg while attempting to activate the patients. The dose of the agent was 300—450 mg (3.5±0.3 mg/kg) when endobronchially injected. Results. The average increase of PaO2/FiO2 after the first maneuver was 152 mm Hg (p<0.05), that of static thoracopulmonary compliance (Cst) was 12.2 ml/cm H2O (p<0.05); intrapulmonary blood shunting (Qs/Qt) reduced by 5% (p<0.05). On trying to activate the patients, PaO2/FiO2, Cst and Qs/Qt stopped differing from the values recorded before the maneuver. After administering surfactant-BL, followed by alveolar mobilization, there were increases in PaO2/FiO2 (by 177 mm Hg), Cst, and Cdyn (by 15.7 and 14 ml/cm H2O, respectively) (p<0.05). In 7 (87.5%) cases, the trachea was extubated within 6 hours after transferring from the operating suite at a PaO2/FiO2 of 350.9±21.4 mm Hg. Acute respiratory distress syndrome was diagnosed in 1 (12.5%) case. Conclusion. Surfactant-BL substantially enhances the efficiency of the alveolar mobilization maneuver in ILOF early after surgery under extracorporeal circulation. The combined use of the surfactant and the maneuver ensures a stable normalization of the biomechanical properties and oxygenizing function of the lung. There are good grounds to believe that the tested tactics plays a therapeutic and prophylactic role in the early signs of acute lung injury. Key words: impaired lung oxygenizing function, acute lung injury, extracorporeal circulation, pulmonary surfactant system, surfactant-BL, alveolar mobilization, artificial ventilation.